Malnutrition and intellectual development: a comparative follow-up study on the effects of early dietary supplementation in a population at risk. - David Edmund Evans (Department of Psychology, 2024)
This investigation attempted to examine the relationship between malnutrition and rGterdstion of intellectual development by comparing children drai.:m f:rarn the sa,ne fumi1ies who ;:rr:st1nt.r:,d voryi11g deg reos of protein-cE,Jorie m,:: lnu t-c iti on during infancy. From each of 14 families 4 children were drawn and assigned respectively to the fol1ou;ing groups: a) kwashior!~or group composed of children who had been admitted to hospital during the first 4 years of life for tre tment of acute Pcm; b) kwashi.o:rkor control g:mup consisting of the nearet,t s:Lb.ling in zge to the kwashiorko:r chiJ.d having no history of ~ictite PCii1; c) the fed group consisting of a later sibJ.ing in tho family in whom malnutrition had been prevented by supplemontary feeding during the first 3 years of life; and d) the fed control group consisting of the sibling in each family just preceding the child who was given supple~entary feeding. A battery of psychological tGsts was adm:i.nistt:n'ed u1h13n the ,nmrn age in the~ kwashiorkor group was 13,0 yGar-s, and 8.9 yec:;;r.'S in thee: fsid group, with the two control Qr.oups taking in -.,:rrnediatg :-:iositions. On mean full-scale int~lligenca ac re th2 f0d group showed a significantly higher difference (p less than 0.01) when compared with the other three groups, The sa~e trend was fou~d for verbal score, although the difference was not quite significant statistically. On non-ver6al score the fed group was not significantly highar than its own contr:oJ. group, but W8S sign1ficantly above tha ktucshicr:!:or group und kweshiorkor control group.. The f,,d ccnt1'ol group was significantly higher than the kwashiorkor group. Analysis of the sub-scale intelligence scores suggested th2t whilst nutritional factors play an isportant part in the determination of the verbal score, an equally important p~rt is played in the determinatio;, of the non-verbal score by :nerJi.c.:al care and environmr:n tal sti mu.lo ti n. The sub- test rssul t5 suggec;tcd a 1:eJ.ation.,. ship b □ twsen malnutrition ond G specific d2ficit in abstract reasoning and learnin; abilities, b~t thi conventional Gsures of 1brain damage' did not discrimina.t0 between the four groups. The deficit in intell ctual development appeared to be rel3ted to the durction of chronic m2lnutrition rather than to the severity F tho insult as indi.csted by an acute s;iisode of kwE,sh~.orkor. The rssults ore discussed in terms of tha failure of campenm:itory sducaticnal progrmns to provide sur,tc,ined elr~v2tion in t:-,e IQ scores of undsr-privilagad children, ood tho suggestion is-~ada that this failure could at least in p8rt be attrib~ted to the operation of nutritional factors ..